Deformation of the Juan de Fuca Plate Beneath the Central Cascadia Continental Margin (44°-45°N) in Response to an Upper Plate Load - Anne M. Tréhu; Kathy Davenport; Christopher B. Kenyon; Suzanne M. Carbotte; John L. Nabelek; Douglas R. Toomey; William S. D. Wilcock (Earth Science, Systems and Society)
A 3D crustal model for the central Cascadia continental shelf and Coast Range between 44°N and 45°N shows that the crystalline crust of the forearc wedge beneath the coastline is characterized by a NW-trending, vertical slab of high-velocity rock interpreted to represent the dike complex that fed the Yachats Basalt, which was intruded into the forearc approximately 37 million years ago. A spatial correlation is observed between downward deflection of the crust of the subducting Juan de Fuca plate, inferred from inversion of PmP arrivals to image the Moho surface, and the high velocity (and consequently high density) anomaly underlying the Yachats Basalt. Apparent subsequent rebound of the subducting plate at greater depth suggests a primarily elastic response of the subducting plate to this load. Calculations for a range of plausible values for the magnitude of the load and the width and depth of the depression indicate that the effective elastic thickness of the subducted Juan de Fuca plate is < 6 km. Although our simple analytical models do not include partial support of the load of the slab by the adjacent upper plate crust or time dependence to account for the motion of the slab beneath the load, incorporation of those effects should decrease rather than increase the apparent strength of the subducted plate. We conclude that the subducted Juan de Fuca plate beneath the central Oregon margin is elastically thin and has the potential to store elastic strain energy before rupturing. Our model of a well-defined, focused and static upper plate load that locally deforms the subducted plate within the nominally seismogenic or transitional part of the Cascadia plate boundary may be unique in providing a relatively straightforward scenario for estimating the mechanical properties of the subducted Juan de Fuca plate. We extrapolate from these results to speculate that elastic deformation of the subducting plate may contribute to the low level of seismicity throughout much of the Cascadia forearc in the inter-seismic period between great earthquakes but note that our local results do not preclude faulting or elasto-plastic deformation of a thin and weak plate as it subducts. These results also suggest that the subducting plate should deform in response to larger scale variations in upper plate thickness and density.